2020
DOI: 10.1136/jitc-2020-000590
|View full text |Cite|
|
Sign up to set email alerts
|

Pre-existing antitherapeutic antibodies against the Fc region of the hu14.18K322A mAb are associated with outcome in patients with relapsed neuroblastoma

Abstract: PurposePatients with cancer receiving tumor-reactive humanized monoclonal antibody (mAb) therapy can develop a human antihuman antibody (HAHA) response against the therapeutic mAb. We evaluated for HAHA in patients with neuroblastoma treated in a phase I study of humanized anti-GD2 mAb (immunoglobulin (Ig)G1 isotype), hu14.18K322A (NCT00743496). The pretreatment sera (collected prior to mAb treatment) from 9 of 38 patients contained antitherapeutic antibodies, even though they had no prior mAb exposure. We sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…More recently, allotypes have been investigated for their potential role as immunogenic motifs in therapeutic antibodies. Surprisingly, it appears that allotypes act only as minor epitopes in monoclonal antibodies and do not appear to elicit acute rejection ( 12 ), although some studies have reported low levels of pre-existing circulating antibodies against allotypes of therapeutic monoclonals ( 13 , 14 ). A key pitfall of serological detection of allotypes is the difficulty of evaluating immunogenic responses to immunoglobulin isotypes expressed at low levels in serum, such as IgE and IgM, signified by a lack of known allotypes for these classes ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, allotypes have been investigated for their potential role as immunogenic motifs in therapeutic antibodies. Surprisingly, it appears that allotypes act only as minor epitopes in monoclonal antibodies and do not appear to elicit acute rejection ( 12 ), although some studies have reported low levels of pre-existing circulating antibodies against allotypes of therapeutic monoclonals ( 13 , 14 ). A key pitfall of serological detection of allotypes is the difficulty of evaluating immunogenic responses to immunoglobulin isotypes expressed at low levels in serum, such as IgE and IgM, signified by a lack of known allotypes for these classes ( 8 ).…”
Section: Introductionmentioning
confidence: 99%